Online Knowledge Sharing in Institutes of Higher Learning: A Malaysian Perspective - Hassandoust, Farkhondeh; Perumal, Vimala (Journal of Knowledge Management Practice, 2011)
The process of knowledge sharing plays a significant role in determining the outcomes of knowledge management in institutions. Electronic communication tools are not specifically considered as repository within knowledge management but are regarded as collaborative tools. For the purpose of improving the results of knowledge sharing through e-communication tools, institutes must understand the mechanisms related to user’s decisions to share knowledge virtually. This study discusses existing researches and develops a theoretical model of factors that influence online knowledge sharing in institutes of higher learning from lecturer’s viewpoint in Malaysia. The aim is to investigate the relationship between influencing factors and online knowledge sharing and improve them for getting better results in academic environments. A questionnaire was designed and distributed through email; the survey was conducted to collect data for this study and multiple regression analysis was chose to analyze the data.
Keywords: Knowledge management; Online knowledge sharing; Institute of higher learning; Malaysia